Properties of Polypropylene and Surface Modified Glass-Fibre Composites. Issue 4 (May 2014) - Zhu, L.H.; Sheng, J.F.; Guo, Z.F.; Ju, X.S.; Li, S.; Chen, Y.F.; Luo, J.
To improve the interfacial bonding between polypropylene (PP) and glass-fibre (GF), the surface modified glass-fibre (SMGF) was prepared with the self-designed sizing containing organofunctional silanes and a copolymer. Then the SMGF-PP composites were prepared and those properties were observed by mechanical testing, light microscopy, X-ray diffractometry (XRD), differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA). Mechanical tests displayed that SMGF-PP composites had an increase in tensile strength, tensile modulus, bending strength, bending modulus and notched impact strength compared to the pure PP. Light micrographs showed that the average fibre length of the composite was 397 μm. XRD data indicated that the crystal size of SMGF-PP composites became smaller compared to pure PP, and β form crystals of PP disappeared with the addition of SMGF to PP matrix. DSC data showed that SMGF could promote the crystallization temperature of PP. TGA analyses showed that the thermal stability of SMGF-PP was better than that of pure PP.